2021
DOI: 10.37077/25200860.2021.34.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Local Concentrated Protein Manufactured from Slaughterhouse Wastes on some Carcasses Traits of Broiler

Abstract: This study was conducted to determine the effect of different levels of local concentrated protein extracted from slaughterhouse wastes on some carcasses traits of broiler. A total of 225 female broiler Ross 308 chicks, one day, were used, randomized distributed into five treatments, with three replicates per treatment (15 chicks each replicate). The treatments were as follows: T1; basal diet contains 4% imported protein. T2; basal diet contains 2% imported protein+2% local manufactured protein. T3; basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
0
1
Order By: Relevance
“…On the contrary, these results were not in the line with the results obtained by [18][19][20][21] who found that body weights were similar in the chicken fed the diet with the local concentrate compared to the imported concentrate.…”
Section: Discussioncontrasting
confidence: 96%
“…On the contrary, these results were not in the line with the results obtained by [18][19][20][21] who found that body weights were similar in the chicken fed the diet with the local concentrate compared to the imported concentrate.…”
Section: Discussioncontrasting
confidence: 96%
“…Increasing phosphorus rates significantly increase available P throughout growing season (table 7) with highest value at rate of 120 kg P ha -1 (table 6). These findings are in agreement with Al-Tamimi et al (2009), Mansoor (2014) and Amruth et al (2017). Application of manure significantly increased the available phosphorus at all growth stages (table 6).…”
Section: Available Phosphorussupporting
confidence: 89%